Atomistic modeling and experimental study of dopant segregation induced morphology transition in ZnO nanoparticles - Panwar, Vishal; Yadav, Navya; Rowthu, Sriharitha; Tewari, Abhishek (Journal of the American Ceramic Society, 2025)
Elemental dopants, commonly introduced during the synthesis of ZnO nanopowders, tend to segregate to surfaces and grain boundaries. However, the atomistic mechanisms underlying dopant segregation and its impact on surface energetics and particle morphology are not yet fully understood. In this study, we combine experimental and computational approaches to investigate Al‐ and Mg‐doped ZnO nanopowders synthesized via the coprecipitation method. Electron microscopy analysis reveals that Al doping transforms the flower‐shaped ZnO particles into granular‐shaped particles and reduces the particle size, whereas Mg doping does not alter the morphology and results into bigger particles. Atomistic modeling of the surface segregation of dopants indicates that Al preferentially segregates to the surfaces, whereas Mg remains in the bulk. These findings are supported by lattice strain calculations from X‐ray diffraction. The preferential segregation of Al to the high energy surfaces results in the homogenization of ZnO surface energies, which is primarily responsible for the observed morphological transformation. This study provides fundamental insights into how Al and Mg dopant segregation influences ZnO nanoparticle's characteristics, offering valuable guidance for designing them for applications in sensing, catalysis, and beyond.